A Case Report: Electrotonic Modulation‐Related T‐Wave Over‐Sensing After Left Bundle Branch Pacing - Linlin Li; Manxin Lin; Jincun Guo; Qiang Li; Fanqi Meng; Xinyi Huang; Simei Chen; Binni Cai (Annals of Noninvasive Electrocardiology)
ABSTRACT A 66‐year‐old male patient diagnosed with dilated cardiomyopathy, heart failure with reduced EF (32%), and complete left bundle branch block (CLBBB) received cardiac resynchronization therapy (CRT)‐D implantation. Left bundle branch pacing (LBBP) was successfully performed, but during the follow‐up 6 weeks later, the electrocardiogram (ECG) showed a sinus rhythm tracked by ventricular pacing with a ratio of approximately 2:1 due to T‐wave over‐sensing, which might be caused by the changes in T‐wave morphology due to electrotonic modulation and hyperkalemia or by the lower sensitivity threshold set by the auto sensing algorithm of the ICD. Shortening post‐ventricular atrial refractory period (PVARP) restored the ventricular pacing tracking of the atrium, and the T‐wave changes improved as time went by.